Three stories in Kagulu, a Bantu language of Tanzania - Petzell, Malin (University of Gothenburg, 2014)
The study comprises five stories told in the Bantu language Kagulu of Tanzania. The stories are available as sound recordings as well as glossed transcriptions. However, the transcriptions do not closely follow the sound recordings but have been normalised in cooperation with a native speaker.

Purpose:

The general aim is to document the Tanzanian minority language Kagulu.

The dataset contains three sound recordings in wave format, three text files containing transcriptions and translations of the sound recordings, one text document explaining the abbreviations used in the glosses and a spreadsheet containing metadata.

Studien omfattar fem berättelser på det tanzaniska bantuspråket kagulu. Berättelserna är tillgängliga som ljudinspelningar och annoterade transkriptioner. Transkriptionerna följer dock inte inspelningarna utan är normaliserade i samarbete med en talare.

Syfte:

Det övergripande syftet är att dokumentera det tanzaniska minoritetsspråket kagulu.

Datasetet omfattar tre ljudinspelningar i wave-format, tre textfiler med transkriptioner och översättningar av ljudfilerna, ett textdokument som förklarar förkortningar i annoteringen och ett kalkylblad med metadata.
Tre berättelser på kagulu, ett bantuspråk från Tanzania
Keywords: minority languages; minoritetsspråk; folklore; folksagor; translation; översättning; linguistics; lingvistik; linguistic analysis; lingvistisk analys; speech; tal (muntligt); literature; litteratur; preservation of cultural property; kulturminnesvård; minority groups; minoritetsgrupp; dialect; dialekt; Bantu languages; bantuspråk; Language and linguistics; Språk och lingvistik; Studies of Specific Languages; Studier av enskilda språk